Classic Psychedelic Coadministration with Lithium, but Not Lamotrigine, is Associated with Seizures: An Analysis of Online Psychedelic Experience Reports - Nayak, Sandeep M.; Gukasyan, Natalie; Barrett, Frederick S.; Erowid, Earth; Erowid, Fire; Griffiths, Roland R. (Pharmacopsychiatry, 2021)
Introduction Psychedelics show promise in treating unipolar depression, though patients with bipolar disorder have been excluded from recent psychedelic trials. There is limited information on the use of classic psychedelics (e. g., LSD or psilocybin) in individuals using mood stabilizers to treat bipolar disorder. This is important to know, as individuals with bipolar depression may attempt to treat themselves with psychedelics while on a mood stabilizer, particularly given enthusiastic media reports of the efficacy of psilocybin for depression.Methods This study analyzed reports of classic psychedelics administered with mood stabilizers from 3 websites (Erowid.org, Shroomery.org, and Reddit.com).Results Strikingly, 47% of 62 lithium plus psychedelic reports involved seizures, and an additional 18% resulted in bad trips while none of 34 lamotrigine reports did. Further, 39% of lithium reports involved medical attention. Most of the lamotrigine reports (65%) but few (8%) of the lithium reports were judged to not affect the psychedelic experience.Discussion Although further research is needed, we provisionally conclude that psychedelic use may pose a significant seizure risk for patients on lithium.
Keywords: psychedelic; lithium; hallucinogen; harm; risks